Respuesta :
Let
C---------> the cost of a pizza
t----------> number of toppings
we know that
$15.74-3t=$14.49-2t
15.74-14.49=3t-2t-------------> t=1.25
the cost of one topping is $1.25
and the cost of one pizza without topping is
15.74-3*1.25--------> $11.99
then
an equation for the cost of a pizza, C, as a function of the number of toppings, t ordered is
C=11.99+1.25t
the answer is
C=11.99+1.25t
C---------> the cost of a pizza
t----------> number of toppings
we know that
$15.74-3t=$14.49-2t
15.74-14.49=3t-2t-------------> t=1.25
the cost of one topping is $1.25
and the cost of one pizza without topping is
15.74-3*1.25--------> $11.99
then
an equation for the cost of a pizza, C, as a function of the number of toppings, t ordered is
C=11.99+1.25t
the answer is
C=11.99+1.25t
Answer:
[tex]f(c)=1.25x+11.99[/tex]
Step-by-step explanation:
Let x be the number of toppings
Let c be the cost of pizza
Cedric got pepperoni, banana peppers, and black olives on his pizza for a cost of $15.74.
Josh ordered mushrooms and eggplant on his pizza and paid $14.49.
As the toppings has the same cost, we can equate the equations:
[tex]15.74-3x=14.49-2x[/tex]
[tex]3x-2x=15.74-14.49[/tex]
x = $1.25
Thus each topping costs $1.25.
And cost of any pizza without topping = [tex]14.49-2(1.25)=11.99[/tex] dollars
So, the function becomes in terms of c ;
[tex]f(c)=1.25x+11.99[/tex]
The base price of pizza is $11.99 and it will increase as the toppings increase.